2016
DOI: 10.1371/journal.pone.0161069
|View full text |Cite
|
Sign up to set email alerts
|

Modestobacter lacusdianchii sp. nov., a Phosphate-Solubilizing Actinobacterium with Ability to Promote Microcystis Growth

Abstract: A novel actinobacterium, designated strain JXJ CY 19T, was isolated from a culture mat of Microcystis aeruginosa FACHB-905 collected from Dianchi Lake, South-west China. 16S rRNA gene sequences comparison of strain JXJ CY 19T and the available sequences in the GenBank database showed that the strain was closely related to Modestobacter marinus 42H12-1T (99.1% similarity) and Modestobacter roseus KLBMP 1279T (99.0%). The isolate had meso-diaminopimelic in the cell wall with whole-cell sugars of mannose, rhamnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Attached bacteria of high cell densities probably compete with Maf for nutrients, which may further inhibit the growth of Maf over a period of time. However, the inhibition ratio decreased with the culture time and the decreasing cell density of the bacteria ( Figure 3 ; Table 2 ), similar to other reports (Zhang et al, 2016a , b ). The results ( Tables 2 , 3 ) showed that the cell density of strain JXJ CY 35 T could be maintained at about 10 5 CFU/ml in cocultures with Maf regardless of the initial inoculation dosages of the bacteria.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Attached bacteria of high cell densities probably compete with Maf for nutrients, which may further inhibit the growth of Maf over a period of time. However, the inhibition ratio decreased with the culture time and the decreasing cell density of the bacteria ( Figure 3 ; Table 2 ), similar to other reports (Zhang et al, 2016a , b ). The results ( Tables 2 , 3 ) showed that the cell density of strain JXJ CY 35 T could be maintained at about 10 5 CFU/ml in cocultures with Maf regardless of the initial inoculation dosages of the bacteria.…”
Section: Discussionsupporting
confidence: 90%
“…Our study indicated that strain JXJ CY 35 T can release available phosphate from both organic and inorganic insoluble P, which is consistent with its gene annotation from GO database ( Supplementary Table S3 ). Therefore, similar to other attached bacteria (Yang and Xiao, 2011 ; Zhang et al, 2016a , b , 2017 ), strain JXJ CY 35 T could dissolve insoluble tricalcium phosphate, and further provided Maf with available phosphate for growth in the absence of available P ( Table 3 ). Strain JXJ CY 35 T can grow in the nitrogen-free medium, indicating that it has N fixing activity and can convert N 2 into NH 3 .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The ability of these three strains and the reference strains M. lapidis DSM 100206 T and M. multiseptatus DSM 44406 T to solubilize insoluble phosphate were determined on plates using phosphate-solubilizing media and confirmed using broth culture method (Zhang et al, 2016), with little modification addressed as follows.…”
Section: Physiological Testsmentioning
confidence: 99%